Optimal monetary policy committee size: Theory and cross country evidence - Szilárd Erhart; Jose-Luis Vasquez-Paz (Magyar Nemzeti Bank, 2007)
Theoretical and empirical studies of different sciences suggest that an optimal committee consists of roughly 5-9 members, although it can swell mildly under specific circumstances. This paper develops a conceptual model in order to analyze the issue in case of monetary policy formulation. The optimal monetary policy committee (MPC) size varies according to the uncertainty of MPC members' information influenced by the size of the monetary zone and overall economic stability. Our conceptual model is backed up with econometric evidence using a 2006 survey of 85 countries. The survey is available for further research and published on the web. The MPC size of large monetary zones (EMU, USA, Japan) is close to the estimated optimal level, but there exist several smaller countries with too many or too few MPC members.
Keywords: E50; E58; 330; monetary policy committe; mpc size; decision making; Geldpolitik; Zentralbank; Arbeitsgruppe; Theorie; Welt